Optimization of Ultrahigh Pressure-Hot Air Drying of Chinese Yam Based on CRITIC Combined with Response Surface Methodology - Cong FU; Baoguo LI; Jun LI; Xiao WANG; Heng LU (Shipin gongye ke-ji)
Objective: The ultra-high pressure (UHP) pretreatment combined with hot air drying (HAD) process of Chinese yam (CY) was established and optimized in this study, in order to shorten the drying time of CY and improve its quality. Methods: The drying time, rehydration ratio (RR), color difference value, polysaccharide and total phenol content (TPC) were used as indicators to investigate the effects of different UHP pressure, holding time and drying temperature conditions on CY processing by single factor experiment, the weight coefficient of five indicators and the comprehensive score under different conditions were calculated by the CRITIC method, using the comprehensive score as the response value to optimize the processing technology of UHP pretreatment combined with HAD by response surface methodology. Results: UHP pretreatment could significantly shorten the drying time (P<0.05) and improve the quality of CY. The weights of drying time, RR, TPC, color difference value and polysaccharide content of CY were 0.34, 0.19, 0.19, 0.14 and 0.14, respectively. The optimal process parameters were determined as follows: Pressure 380 MPa, holding time 9 minutes, drying temperature 50 ℃. Under these conditions, the results of the validation experiment for each indicator were drying time of 400±17.32 min, RR of 2.18±0.04 g/g, color difference value of 6.02±0.18, polysaccharide content of 78.08±1.33 mg/g, TPC of 2.77±0.16 mg/g, and comprehensive score of 74.75±2.40. The relative standard deviation (RSD) between the validation result and the predicted value was 2.71%, indicating that the model had good predictability. Conclusion: This study established an efficient and energy-saving UHP-HAD drying process of CY, which would provide new ideas for the standardized research and application of CY processing.